Diabetes and intervertebral disc degeneration: A Mendelian randomization study - Jin, Peihao; Xing, Yonggang; Xiao, Bin; Wei, Yi; Yan, Kai; Zhao, Jingwei; Tian, Wei (Frontiers in Endocrinology, 2023)
Abstract Introduction: Intervertebral disc degeneration (IVDD) is an important contributor of low back pain, which represents one of the most disabling symptoms within the adult population. Recently, increasing evidence suggests potential association between Type 2 Diabetes Mellitus (T2DM) and IVDD. However, the causal relationship between these two common diseases remains unclear. Methods: We conducted a two-sample Mendelian randomization (MR) analysis to assess the causal association between T2DM and IVDD. Sensitivity analysis was performed to test for heterogeneity and horizontal pleiotropy. Multivariable MR was also conducted to adjust for the effect of BMI on IVDD. Results: 128 independent SNPs that were significantly associated with T2DM were selected as instrumental variables in univariable MR analysis. Our results showed that patients with T2DM had a higher risk of developing IVDD (OR, 1.069; 95% CI, 1.026-1.115; p=0.002). The relationship remained stable in sensitive analysis including multivariable MR, which implicated the direct causal effect of T2DM on IVDD (OR, 1.080; 95% CI, 1.041-1.121; p < 0.001) after adjusting for BMI. Conclusions: MR analysis indicated a causal effect of T2DM on IVDD, and the effect persisted even when we accounted for the impact of BMI.